Assistência farmacêutica em unidades prisionais na Paraíba - Cardins, Karla Karolline Barreto (2017)
Introduction: The implementation of the Unified Health System represented a major advance in the health care policy of the Brazilian population, increasing access to c are networks and consequently to pharmaceutical care. This guarantee also includes the penitentiary system, however, the chronic situation of unhealthy, the higher prevalence of health problems and the difficulty of the population's access to medicines compromise the assistance. Objective: Analyze the pharmaceutical assistance in penitentiaries in the state of Paraíba considering the appropriate prescription and dispensation of essential and strategic medicine. Methodological approach: A descriptive, cross-sectional and qualitative study carried out in seven penitentiaries in the state of Paraíba between February and August of 2016. A survey was carried out in the medical records to verify the prescription of essential and strategic medicines and a local inspection was carried out to evaluate the installations of the places destined to the medicines dispensation. Health professionals and patients were interviewed through a semi-structured and audiograved interview. And the results were categorized and analyzed from a content analysis perspective. Results: Access to the medicine was studied according to their acquisition, as well as the barriers found to guarantee continuous treatment, the rational use was evaluated by means of adequate prescription, supervision of the necessary doses and the storage of medicines and the dispensation was defined by the prescription delivery, the guarantee of the receipt of the medicines within the standards of quality and safety and the guidelines related to the use. It was found that a large part of the penitentiaries have been responsible for providing the medications, however, the prisoners are practically not receiving the revenues, are not guided by suitable professionals and are also not supervised during the taking of the doses. In addition, most penitentiaries do not have a pharmacy and the dispensing process is limited by the prison environment and the lack of trained professionals. Conclusions: It is perceived that the guarantee of pharmaceutical assistance should be a permanent concern of public health policies, since even with a lack of essential and strategic medicines, adequate prescription, dispensing, supervisi on of the doses taken, correct storage and follow-up to ensure continuity of treatment are neglected, in addition to the precarious physical structure and lack of professionals needed and trained for the prison system. Thus, the findings contribute to management gaining insight into the current reality of pharmaceutical care in penitentiaries and for health teams to deepen their knowledge in the area.